Kings and prophets : 1 Samuel 16:23-1 Kings 21:8. - Hoth, Iva (Her The picture Bible for all ages ;, 1973)
Retells in comic book format the Old Testament stories from David's fight with Goliath to the time of the Prophet Elijah.